Development Media Learning Based on Interactive Multimedia Using Macromedia Director MX - Rianita Simamora; Cahyo Hasanuddin; Gading Bendito Simangunsong; Tiurlina Siregar; Michaela Haug (PT. TAROMBO RESEARCH DEVELOPMENT pak, 2026)
Improving the quality of education is a very important concrete element. in effort improvement quality resource man. In line with That, the thing that very important For noticed is a problem performance learning. Problems A common problem that is often faced by students, especially university students, is that there are still quite a lot of them who have not been able to achieve satisfactory learning achievements. The learning process at Gunadarma University extends beyond classroom sessions and also utilizes multimedia-based learning media. However, multimedia-based learning is one-way. Based on the problems above, interactive multimedia-based teaching materials were created. called learning media for basic concepts of Image Processing This application presents material interactively accompanied by animation, audio, video. and is equipped with evaluations in the form of practice questions. The results achieved from the creation of this learning media are that students can understand the Image Processing course. It is hoped that this application will facilitate the teaching and learning process and improve the quality of learning achievement